The Construction Path and Mode of Public Tourism Information Service System Based on the Perspective of Smart City. (23rd November 2020) - Ma, Hongyan
Abstract : Under the framework of smart city, starting from the demand for urban public tourism information services, drawing on the new public service theory, customer perceived value theory, and basic information service theory, combined with previous research results, using literature analysis, questionnaire survey, and other methods, and starting from the carrier level of the public tourism information service system, this study analyzed the public tourism information services in detail. This study combed the current status quo and problems of the public tourism information service system for qualitative analysis and summed up some common shortcomings and deficiencies. Along with the results of the questionnaire, this paper analyzed the existing problems in the current public tourism information service system and identified the demands of tourists for public tourism information services. Based on this, the research puts forward the idea of constructing the public tourism information service system under the background of smart city, including the system framework, characteristics, service media and mode, operation mode, management mechanism, and other aspects. The study concluded that there is a need to construct theoretical and research models of the impact of public tourism services on the quality of destination from the perspective of smart city, to use the structural equation model for quantitative analysis, to verify the model hypothesis, and to consider that public tourism services have a significant positive impact on the behavioral and psychological responses of tourists. On the basis of combing the literature and starting from the overall situation, this study puts forward a systematic integration idea, which is of theoretical significance.